International rules for trade in natural resources - Paul Collier; Tony Venables (World Trade Organization (WTO), 2010)
This paper investigates the scope for international rules to address market failures in trade in natural resources and the associated international transactions of prospecting and investment in resource exploitation. We argue that several market failures are likely to have substantial costs. However, due to the distinctive features of natural resources, the market failures are particular to them. The ad hoc approaches which have attempted to address them to date leave scope for a more systematic and comprehensive approach by the WTO, but the distinctive features of natural resources imply that this could not simply be an application of the rules appropriate for other forms of trade.
Keywords: 330; Rohstoffressourcen; Erschöpfbare Ressourcen; Außenhandel; Gewinn; Wirtschaftswachstum; Terms of Trade; WTO-Regeln; Welt